1977
DOI: 10.1080/00071667708416367
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, physiological and production indices related to fat metabolism in the laying fowl at various stages of physiological development

Abstract: The significance of fat accumulation during physiological development of layers was studied using White Leghorn X Australorp pullets from 12 weeks of age. 2. Liver fat, carcass fat, liver weight and body weight increased markedly at the onset of sexual maturity. 3. Within the liver, the protein to DNA ratio did not alter significantly during development; glycogen was not consistently depleted by egg production. 4. Liver fat content was significantly correlated with carcass fat, liver weight and DNA concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“… E Birds: Patel et al, 1977 ; Desmeth, 1981 ; Hermier et al, 2003 ; Wan et al, 2018 . F Mammals: Ralli et al, 1941 ; Kwiterovich et al, 1970 ; Neill et al, 1977 ; Christie, 1985 ; Hall et al, 1997 ; Wang et al, 2000 ; Cable et al, 2009 ; Fernando et al, 2012 ; Tajik et al, 2012 ; Siques et al, 2014 ; U.S. Department of Agriculture, Agricultural Research Service [USDA ARS], 2020 . G Neill et al, 1977 ; Patel et al, 1977 ; Desmeth, 1981 ; Wang et al, 2000 ; Hermier et al, 2003 ; Wan et al, 2018 ; U.S. Department of Agriculture, Agricultural Research Service [USDA ARS], 2020 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… E Birds: Patel et al, 1977 ; Desmeth, 1981 ; Hermier et al, 2003 ; Wan et al, 2018 . F Mammals: Ralli et al, 1941 ; Kwiterovich et al, 1970 ; Neill et al, 1977 ; Christie, 1985 ; Hall et al, 1997 ; Wang et al, 2000 ; Cable et al, 2009 ; Fernando et al, 2012 ; Tajik et al, 2012 ; Siques et al, 2014 ; U.S. Department of Agriculture, Agricultural Research Service [USDA ARS], 2020 . G Neill et al, 1977 ; Patel et al, 1977 ; Desmeth, 1981 ; Wang et al, 2000 ; Hermier et al, 2003 ; Wan et al, 2018 ; U.S. Department of Agriculture, Agricultural Research Service [USDA ARS], 2020 .…”
Section: Resultsmentioning
confidence: 99%
“… F Mammals: Ralli et al, 1941 ; Kwiterovich et al, 1970 ; Neill et al, 1977 ; Christie, 1985 ; Hall et al, 1997 ; Wang et al, 2000 ; Cable et al, 2009 ; Fernando et al, 2012 ; Tajik et al, 2012 ; Siques et al, 2014 ; U.S. Department of Agriculture, Agricultural Research Service [USDA ARS], 2020 . G Neill et al, 1977 ; Patel et al, 1977 ; Desmeth, 1981 ; Wang et al, 2000 ; Hermier et al, 2003 ; Wan et al, 2018 ; U.S. Department of Agriculture, Agricultural Research Service [USDA ARS], 2020 . H Ralli et al, 1941 ; Kwiterovich et al, 1970 ; Christie, 1985 ; Hall et al, 1997 ; Helbig, 2006 ; Cable et al, 2009 ; Siques et al, 2014 ; U.S. Department of Agriculture, Agricultural Research Service [USDA ARS], 2020 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in their study, Neill et al (1975) confirmed that the reticulosis was a definitive lesion of FLHS in Queensland, where the outbreaks were considered not to be associated with any known toxic principle. It is known that reticulosis produces a structural weakness of the liver which will rupture when under stress (nutritional/toxic, infectious, or environmental) (Neill et al, 1977). However, any correlation between liver fat content and degree of lysis of the reticulin was not found, although the presence of heavy fat infiltration in a structurally weakened liver was thought to have been the reason for massive haemorrhage and death of hens (Neill et al, 1975).…”
Section: An "Old" Disease In Queensland Flocksmentioning
confidence: 94%